Arsenic, Chromium, and Other Potentially Toxic Elements in the Rocks and Sediments of Oropos-Kalamos Basin, Attica, Greece - D. Alexakis; D. Gamvroula (Applied and Environmental Soil Science)
Rocks and sediments are non-anthropogenic sources of elements contamination. In this study, a series of potentially toxic elements were quantified in rocks and sediments of the Oropos-Kalamos basin. Only As, Hg, Pb, and Sb contents, in all the examined rocks and sediments, were higher than the levels given in international literature. Concentration of the elements As, Cr, Hg, Mo, Ni, and U is highly elevated in the lignite compared to crustal element averages. The enrichment of Cr and Ni in the lignite can be attributed to the known ultramafic rock masses surrounding the basin, while enrichment of As, Hg, Mo, Sb, and U is associated with the past geothermal activity of the Upper Miocene (about 15 million years ago). Nickel and Cr were transported into the lignite deposition basin by rivers and streams draining ultramafic rock bodies. The results of this study imply the natural source of Cr3+ and Cr6+ contamination of the Oropos-Kalamos groundwater, since high Cr contents were also recorded in the lignite (212.3 mg kg−1), chromiferous iron ore occurrences (256.6 mg kg−1), and alluvial deposits (212.5 mg kg−1), indicating Cr leaching and transportation to the depositional basin dating from the Upper Miocene age.